1984
DOI: 10.1111/j.1600-0404.1984.tb07797.x
|View full text |Cite
|
Sign up to set email alerts
|

Are right-hemisphere lesions really larger? Lesion size and laterality in meningioma patients

Abstract: Patients with pathologically confirmed diagnoses of meningioma were examined to investigate the hypothesis that left-hemisphere lesions are smaller or declared earlier than right-hemisphere lesions. 77 patients were examined with regard to age at presentation and nature of symptoms. In addition CAT scan films of 47 patients were obtained for measurement of lesion size. There were no differences between right and left lesion groups with regard to size of lesion or age at presentation. Subgroups of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2003
2003
2003
2003

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
2
1
1
Order By: Relevance
“…Other authors have reported a left-sided predominance for meningioma, but the sample size was small (L:R = 1.50; n = 65) [31] or not reported [10]. We observed a nonsignificant 1% excess of right-sided over left-sided glioma, and a 9% excess of left-sided over right-sided meningioma.…”
Section: Weakness Hemiparesis or Numbnesscontrasting
confidence: 33%
See 2 more Smart Citations
“…Other authors have reported a left-sided predominance for meningioma, but the sample size was small (L:R = 1.50; n = 65) [31] or not reported [10]. We observed a nonsignificant 1% excess of right-sided over left-sided glioma, and a 9% excess of left-sided over right-sided meningioma.…”
Section: Weakness Hemiparesis or Numbnesscontrasting
confidence: 33%
“…This is based on the presumption that effects on parts of the brain involved with language and speech are likely to produce symptoms more noticeable or upsetting to the individual or to family members, and thus lead to earlier diagnosis [31]. In the present study, the mean size of left-sided, high-grade glioma at the time of diagnosis was significantly smaller than the mean size of right-sided, high-grade glioma.…”
Section: Weakness Hemiparesis or Numbnessmentioning
confidence: 44%
See 1 more Smart Citation
“…Στην προσπάθεια τους να προσεγγίσουν καλύτερα το πραγματικό μέγεθος του όγκου, πολλοί ερευνητές χρησιμοποίησαν στο παρελθόν διάφορα στερεομετρικά μοντέλα, υποθέτοντας ότι το σχήμα του όγκου είναι σφαιρικό, ελλειπτικό ή ακόμα και ορθογώνιο παραλληλεπίπεδο (55,56,57). Ούτε όμως αυτή η μέθοδος αποδίδει τον πραγματικό όγκο ενός νεοπλάσματος.…”
Section: ογκομετριαunclassified